Factors affecting non-intention to invest in peer-to-peer lending platform towards youth investors in Malaysia - Kong, Bi Xuan; Lee, Hao Cheng; Mak, Juen Wei; Wong, Yu Qian (2024)
Peer-to-Peer (P2P) lending has become a major alternative financing method, linking borrowers directly with investors via online platforms. Despite the rise of P2P lending in Malaysia, there remains a lack of understanding about the factors that influence lending decisions in this developing market. This research project focuses on examining the dynamics of P2P lending, with a focus on the factors that influence investment decisions, especially among young investors. since youth investors often embrace new technologies and opportunities, making them crucial for the growth and sustainability of the P2P lending industry. Using purposive sampling method, the survey data for this project was gathered from 400 youth investors across various states in Malaysia who expressed interest in investing in online P2P platforms by questionnaires. Partial Least Squares-Structural Equation Modelling was conducted for estimation purposes using PLS-SEM. Based on Extended Technology Acceptance Model (TAM) and Unified Theory of Acceptance and Use of Technology (UTAUT 2), this study aims to explore the non-intention to invest in P2P lending platforms, effort expectancy, performance expectancy, perceived risk, facilitating condition, social influence and the moderating effect of perceived risk among youth investors in Malaysia. The findings showed that facilitating condition, social influence and performance expectancy has significantly influence toward non intention in P2P lending platform. Hence, these findings highlight the need for learning resources and guidance for youth investors, as well as the necessity for local government programs that promote the awareness to invest in P2P lending platforms.